(untitled) (International journal of artificial intelligence, 2026)
The integration of economics-based terminology into Russian language instruction represents a targeted approach to teaching Russian as a foreign language (RFL), particularly for students specializing in economics, business, and finance. This method enhances professional communicative competence by linking linguistic skills with domain-specific knowledge, addressing the growing demand for bilingual specialists in post-Soviet contexts such as Uzbekistan. Drawing on corpus-based word lists, interactive methodologies, and comparative analyses of English-Russian economic discourse, the study demonstrates that economics terminology—encompassing both traditional and post-perestroika terms—facilitates faster mastery of specialized texts and real-world communication. Key findings highlight a corpus-derived Russian Economics Word List (REWL) comprising 507 lemmas that significantly boosts text coverage, alongside interactive techniques like case studies, role-playing, and multimodal resources that overcome challenges such as term heterogeneity and polysemy. In Uzbek higher education settings, these strategies foster interdisciplinary learning, improving speech culture and professional readiness. The research underscores the dynamic nature of economic terminology and its pedagogical value in non-linguistic universities, offering practical recommendations for curriculum design. Overall, economics-based terms serve as an effective bridge between language acquisition and professional application, with implications for global LSP (Language for Specific Purposes) teaching.